Predictive Efficacy of MiR-125b-5p, MiR-17-5p, and MiR-185-5p in Liver Metastasis and Chemotherapy Response Among Advanced Stage Colorectal Cancer Patients - Sur, Daniel; Balacescu, Loredana; Cainap, Simona S.; Visan, Simona; Pop, Laura; Burz, Claudia; Havasi, Andrei; Buiga, Rares; Cainap, Calin; Irimie, Alexandru; Balacescu, Ovidiu (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs), a class of small non-coding RNAs represent potential biomarkers for colorectal cancer (CRC). The study hypothesized that miRNAs associated with liver metastases may also contribute to assessing treatment response when associated to plasma exosomes. In this study, we used two sets of biological samples, a collection of tumor tissues harvested from patients with CRC with and without liver metastases, and a collection of plasma from CRC patients with and without response to FOLFOX4/FOLFIRI regimens. We investigated 10 target miRNAs in the tissue of 28 CRC patients with or without liver metastases and identified mir-125b-5p, miR-17-5p, and miR-185-5p to be associated to liver metastasis. Further we investigated the three miRNAs, in a plasma collection, at the exosomal level to test their association with chemotherapy response. The expression of miR-17-5p significantly increased in the non-responders compared to that among the partial responders in FOLFOX4 or FOLFIRI treatment. The high expression of miR-185-5p statistically correlated with a lack of response only in FOLFIRI therapy. The miR-125b-5p plasma exosomes demonstrated a good correlation with high tumor grade and stage. The three miRNAs showed a statistically significant correlation with liver metastasis and treatment response of advanced CRC patients.